The high-performance work practice and job embeddedness among the frontline hotel employees in Malaysian context / Norhamizan Hamir … [et al.] - Hamir, Norhamizan; Mohd Kamil, Nurul Liyana; Ahmad, Zamri; Ahmad Ridzuan, Ahmad Hidayat; Abdul Rahim Siddiqe, Ashraf Siddik Khan (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This study will examine the relationship between high-performance work practice (HPWP) which is construed as service training, empowerment, and rewards upon job embeddedness. Data were obtained from a self-administered questionnaire that was distributed to frontline hotel employees in four and five-star hotels in Malaysia. A Partial Least Squares Structural Equation Modelling (PLSSEM) was employed to analyze the data. The result revealed that the empowerment and rewards were significantly related to the job embeddedness but service training was found to be insignificant. The study revealed that when the management of the hotel provides their employees with empowerment and rewards, the employees tend to show compatibility and comfort with the organization at the same time does not willing to sacrifice the benefit they currently receive by leaving their job. Implications of the results and further research avenues are discussed.